The acute adaptation of skin microcirculatory perfusion in vivo does not involve a local response but rather a centrally mediated adaptive reflex - Monteiro Rodrigues, Luís; Rocha, Clemente; Andrade, Sérgio; Granja, Tiago; Gregório, João (Frontiers in Physiology, 2023)
Cardiovascular homeostasis involves the interaction of multiple players to ensure a permanent adaptation to each organ’s needs. Our previous research suggested that changes in skin microcirculation - even if slight and distal - always evoke an immediate global rather than “local” response affecting hemodynamic homeostasis. These observations questioned our understanding of known reflexes used to explore vascular physiology, such as reactive hyperemia and the veno-arteriolar reflex (VAR). Thus, our study was designed to further explore these responses in older healthy adults of both sexes, and to potentially provide objective evidence of a centrally mediated mechanism governing each of these adaptive processes. Participants (n=22, 52.5 ± 6.2 years old) of both sexes were previously selected. Perfusion was recorded in both feet by laser Doppler flowmetry (LDF) and photoplethysmography (PPG). Two different manoeuvres with opposite impacts on perfusion were applied as challengers to one single limb - reactive hyperemia evoked by massage and a single-leg pending to generate a VAR. Measurements were taken at baseline (Phase I), during challenge (Phase II), and recovery (Phase III). A 95% confidence level was adopted. Six other young healthy women were selected to provide video-imaging by optoacoustic tomography (OAT) of a supra-systolic post-occlusive reactive hyperemia (PORH) in the upper limb. Hyperemia as VAR modified perfusion in both limbs in each case detected by LDF and PPG, changing systemic hemodynamics in all participants. Comparison with previously published data obtained under the same conditions in a younger cohort revealed that results were not statistically different between groups. The OAT documentary and analysis showed that the suprasystolic pressure in the arm displaced blood, in the forearm, from the superficial to the deeper plexus vessels. Deflation allowed the blood to return and be distributed in both plexus. These responses, centrally mediated and determined by the need to reestablish the limb circulatory homeostasis modified by the challenger, were present in all individuals, independent of age. Therefore, a new mechanistic interpretation of these exploratory manoeuvers is needed to better explore and characterize in vivo cardiovascular physiology in human.